2013
DOI: 10.1080/01694243.2012.758575
|View full text |Cite
|
Sign up to set email alerts
|

New heat-resistant polytriazole adhesives: investigation of adhesion of polytriazole resins to metals

Abstract: Crosslinkable polytriazole resins (CPTs) were synthesized by 1,3-dipolar cycloaddition reaction between azide and alkyne monomers. Adhesion properties of CPTs and an epoxy resin to different metal substrates (copper, iron and aluminium) were evaluated in terms of the tensile lap shear strength. CPTs to aluminium and iron substrates have higher adhesion strength than those to copper substrates. The effect of temperature and humidity on adhesion strength has been investigated. The resin CPT-3 has the best heat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This process is a reliable method for the rapid assembly of functional molecules, being highly tolerant to variations in the nature of the components and the reaction conditions used to join them. Taking advantage of the well‐known property of triazoles to bind to metal surfaces, and the availability of catalytically active Cu(I) at the surface of metallic copper in air, we previously used CuAAC chemistry to create strong adhesives between copper‐containing surfaces . We suggested that an important aspect of the underlying chemistry is the kinetic lability of the Cu(I)–triazole interaction, allowing the diffusion of Cu(I) ions through the developing polytriazole network, similar to radical diffusion in addition polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…This process is a reliable method for the rapid assembly of functional molecules, being highly tolerant to variations in the nature of the components and the reaction conditions used to join them. Taking advantage of the well‐known property of triazoles to bind to metal surfaces, and the availability of catalytically active Cu(I) at the surface of metallic copper in air, we previously used CuAAC chemistry to create strong adhesives between copper‐containing surfaces . We suggested that an important aspect of the underlying chemistry is the kinetic lability of the Cu(I)–triazole interaction, allowing the diffusion of Cu(I) ions through the developing polytriazole network, similar to radical diffusion in addition polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has been engaged in the preparation and modification of high performance PTAs and their derivatives since 2002. 26 31 A series of thermosetting PTA resins with good heat resistance and high mechanical properties have been explored .…”
Section: Introductionmentioning
confidence: 99%